Risk of hepatocellular carcinoma in adults exposed to oral antidiabetic drugs: a systematic review - Shadman Newaz; Monami Ahmed; Snigdho Hritom Sil; Mst Samanta Hoque; Mehbub Hossain; Tonima Tabassum Dola; AfIa Anjum Tangail; Sohana Nasrin; Ayesha Noor (Journal of Current Oncology and Medical Sciences)
Introduction: An increasing amount of clinical research is being conducted on the association between antidiabetic medications and the outcomes of hepatocellular carcinoma. By offering a thorough synthesis of the available data and pinpointing topics for further investigation, this systematic review seeks to assess any possible correlations between the results. Methods: According to a registered protocol on the Open Science Framework, we carried out a systematic review of research published between January 2015 and February 2025. We reviewed several databases to identify English-language research employing a range of study designs, including observational studies, cohort studies, and clinical trials. After a thorough screening procedure, 18 studies were chosen from 1089 records. Following the parameters of this study, the main objective was to summarise the evidence without doing a formal quality assessment. Results: Our analysis found possible connections between liver cancer outcomes and several antidiabetic groups, including insulin, metformin, thiazolidinediones, sodium-glucose cotransporter 2 (SGLT2) inhibitors, GLP-1 receptor agonists, and DPP-4 inhibitors. Metformin, GLP-1 receptor agonists, and SGLT2 inhibitors were consistently associated with reduced risk of hepatocellular carcinoma (HCC) and improved survival outcomes. In contrast, insulin use in cirrhotic patients was linked to increased all-cause mortality and higher liver-related complications. Thiazolidinediones showed a time-dependent protective effect, with longer use correlating with lower HCC risk. The results suggest that some antidiabetic drugs may affect overall survival, recurrence rates, and mortality specific to liver cancer. We discovered that rather than being an initiating factor, the majority of antidiabetic medications have decreased the risk of liver cancer. Conclusion: This systematic review contributes to a better understanding of the complex relationship between antidiabetic medications and liver cancer outcomes. Important conclusions imply that medical professionals ought to think about the possible effects of particular antidiabetic medications in liver cancer patients. More extensive randomised controlled trials with longer follow-up are advised to elucidate these correlations and guide treatment recommendations.